The Image of Bharatiya Nari as Projected by Indian Television Soap-Operas - SHASWATI DAS (Dr. Chinmay Pandya, 2016)
Television soaps and serials in private television channels have swept the Indian market in the last few decades. These soap operas have been upholding the socio-cultural patterns of the country through their contents. In the construction of Indian cultural landscape Indian women and their roles in society are the most vulnerable sites. The linkage of national identity and tradition with Indian women's roles in society places them in a problematic position, given the patriarchal nature of Indian society. Soap operas on Indian television mostly depict women as homely and tradition-bound. Though there are portrayals of educated, professional women but they are also shown to find solace in the family. This paper tries to trace the image of the Indian Woman that has been endorsed by the Indian soap operas since its beginning and in doing so it tries to explore the implications of certain myths and ideologies that drive the story writers and the producers to de-recognize the changes in the contemporary society and to fall back on projecting stereotypical images; thus giving preference to social identity while ignoring individual identity of a woman.